Confronting plastic pollution to protect environmental and public health. - Liza Gross; Judith Enck (PLoS Biology)
A new collection of evidence-based commentaries explores critical challenges facing scientists and policymakers working to address the potential environmental and health harms of microplastics. The commentaries reveal a pressing need to develop robust methods to detect, evaluate, and mitigate the impacts of this emerging contaminant, most recently found in human placentas.